Modified ant colony clustering method in long-term electrocardiogram processing - Burša, Miroslav; Lhotská, Lenka (Conference proceedings ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2007)
The paper presents an application of a clustering technique inspired by ant colony metaheuristics. The paper addresses the problem of long-term (Holter) electrocardiogram data processing. Long-term recording produces a huge amount of biomedical data, which must be preprocessed prior to its presentation to the specialist. The paper also discusses relevant aspects improving the robustness, stability and convergence criteria of the method. The method is compared with well known clustering techniques (both classical and nature-inspired), first testing on the known dataset and finally applying them to the real ECG data records from the MIT-BIH database and outperforms the standard methods. Electrocardiogram data clustering can effectively reduce the amount of data presented to the cardiologist: cardiac arrhythmia and significant morphology changes in the ECG can be visually emphasized in a reasonable time. The final evaluation of the ECG recording must still be made by an expert.
Keywords: financování organizované; Animals; Signal Processing, Computer-Assisted; elektrokardiografie ambulantní; Ants; počítačové zpracování signálu; diagnóza počítačová; Reproducibility of Results; shluková analýza; lidé; chování zvířat; Formicidae; Sensitivity and Specificity; senzitivita a specificita; Arrhythmias, Cardiac; Algorithms; Pattern Recognition, Automated; srdeční frekvence; Financing, Organized; Heart Rate; rozpoznávání automatizované; biomimetika; reprodukovatelnost výsledků; algoritmy; Behavior, Animal; Electrocardiography, Ambulatory; zvířata; Cluster Analysis; Diagnosis, Computer-Assisted; Biomimetics; srdeční arytmie; Humans